We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
91
1
avatar

http://prntscr.com/mt6er7

 Mar 4, 2019
 #1
avatar+104627 
+1

y = x^2 -3x + 7

y = 3x - 2

 

Set the y's equal

 

x^2 - 3x + 7 =  3x - 2        add2, subtract 3x from both sides

 

x^2 - 6x + 9 = 0         factor

 

(x - 3)^2 = 0        take the square root

 

x - 3 = 0        add 3 to both sides

 

x = 3

 

Put this into either function to find the y coordinate......3(3) - 2 = 9 - 2 = 7

 

 

cool cool cool

 Mar 4, 2019

27 Online Users

avatar
avatar
avatar